The Augustan temple and forum of the colony of Barcino: a 90 degree turn - Orengo, Hèctor A.; Cortés, Ada (John Wiley & Sons Ltd., 2014)
The Augustan Roman temple at Barcino has been a key element during the last 60 years in the research of the colony's urban development. Its peculiar elongated and narrow plan, first proposed in 1835, and its location at the highest point of the ancient city have dictated our understanding of the urban layout of Barcino by conditioning the shape of the city's forum and affecting the interpretation of the archaeological excavations carried out in the area since then. This paper proposes an alternative plan of the temple, based on data drawn from recent archaeological excavations, topographical analysis, typological comparisons, and the study of written sources. Our alternative hypothesis for the temple permits an in-depth reinterpretation of the plan of the forum and the evolution of the urban plan.